Early and Midterm Results after Endovascular Repair of Non-infected Saccular Lesions of the Infrarenal Aorta. (June 2022) - Lomazzi, Chiara; Piffaretti, Gabriele; D'Oria, Mario; Benedetto, Filippo; Stilo, Francesco; Mezzetto, Luca; Franchin, Marco; Trimarchi, Santi; Bissacco, Daniele; Savarè, Laura; Cavi, Raffaella; et al.
Abstract : Objective: The aim was to report short and midterm outcomes of a cohort of consecutive patients treated by endovascular aortic repair (EVAR) for saccular lesion of the abdominal aorta (sl-AA). Methods: This was a multicentre, retrospective, financially unsupported physician initiated, observational cohort study that involved tertiary referral from Italian hospitals. For this study, between January 2010 and December 2020, only those patients treated by EVAR for non-infected sl-AA, namely blister/ulcer like projection and/or penetrating aortic ulcer, were analysed. Primary outcomes of interest were overall survival and freedom from aorta related mortality (ARM). Results: The final cohort included 120 of 3 982 eligible aortic lesions. There were 103 (85.8%) males and 17 (14.2%) females. The median age was 76 years (interquartile range [IQR] 69, 80). Rupture on admission was observed in 10 (8.3%) cases. Early (≤ 30 days) death occurred in two (1.7%) patients. There were five (4.2%) complications requiring surgical re-intervention (iliac limb occlusion n = 4; groin haematoma, n = 1). The median duration of follow up was 20 months (IQR 4, 59.5): the estimated overall survival was 85.5% (standard error [SE] 0.035; 95% confidence interval [CI] 77.3 – 91.1) at 12 months, 78.7% (SE 0.044; 95% CI 69.0 – 86.0) at 36 months, and 74% (SE 0.050; 95% CI 63.2 – 82.5) at 60 months. Only one (0.8%) patient required aortic re-intervention during follow up because of a late endograft infection. The estimated freedom from ARM was 96% (SE 0.050; 95% CI 90.3 – 98.2) at 36 and 60 months. Cox's regression analysis identified that death was associated with age > 70 years (hazard ratio [HR] 1.10; 95% CI 1.04 – 1.17, p = .001), and coronary artery disease (HR 1.14; 95% CI 1.04 – 1.26, p = .006). Conclusion: EVAR for sl-AA proved to be safe and effective. The mortality rate was low for a group of patients known to be at high risk from open repair, and EVAR remained stable with no ARM during midterm follow up, and an acceptably low 0.8% endograft related re-intervention rate.